Assessing the relative contribution of Moral Foundation Theory, Right-Wing Authoritarianism, and Social Dominance Orientation in the prediction of political orientation - Ballout, Mouhamad Houssein; Briggs, Amy; Armstrong, Jacob; Brendan Clark, Charles (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
Right-Wing Authoritarianism (RWA) and Social Dominance Orientation (SDO) are two constructs which have been demonstrated to explain differences in political orientation as well as opinions concerning how society should be structured. More recently, Moral Foundations Theory (MFT) has demonstrated its ability to also delineate between political and social groups. Past research, however, has presented an unclear image of how RWA, SDO, and MFT interact with their influence on political orientation. In order to provide firmer grounding, this study examined the relationship between these three constructs as well as their ability to predict political orientation and perceived threat towards immigrants in a student sample (N = 300). Large correlations were found between SDO, RWA, and MFT. A path analysis was conducted to determine the relationship between political orientation, perceived threat towards immigrants with SDO, RWA, and MFT. Basic demographics were also considered. Several models were assessed, the model containing SDO, RWA, as well as MFT best fit the data. Furthermore, MFT demonstrated significant pathways with both political orientation and perceived threat towards immigrants. Our finding suggest that MFT contributes to the explanation of political orientation beyond the variance accounted for by SDO and RWA.